Strategi Komunikasi Pemasaran Tim Editing Video Dalam Meningkatkan Engagement Konten Promosi Es Krim Double G Di Instagram - Rahman, Dany Alif; Murtiadi Murtiadi; Arista, Roynaldi (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze video editing strategies in enhancing engagement for Double G ice cream promotional content on Instagram. Social media platforms, particularly Instagram, have become effective marketing channels, requiring brands to produce creative content that attracts audience interaction. In this context, promotional videos play a crucial role, while the editing process serves as the key to creating both visual and emotional appeal. The research employs a descriptive qualitative method involving the business owner, content creator team, and active consumers of Double G Instagram account as subjects. Data were collected through interviews, observations, and documentation, then analyzed using coding, theme categorization, and conclusion drawing. The findings reveal that Double G video editing strategies implicitly apply the concept of Segmentation, Targeting, and Positioning (STP), targeting young audiences who are active and trend-sensitive. This is achieved through engaging visuals, cheerful music, and a personal communication style. Moreover, the editing strategy aligns with the stages of the AIDA model (Attention, Interest, Desire, Action). Strong visuals and upbeat music successfully capture attention, behind-the-scenes content generates interest, appetizing product displays stimulate desire, and participation calls encourage action.